The Relationship Between Gratitude and Psychological Well-being of Street Vendors at the Sidoarjo Sports Hall: Hubungan Antara Syukur dengan Kesejahteraan Psikologis pada Pedagang Kaki Lima di GOR (Gelanggang Olah Raga) Sidoarjo - Etdika, Yovi Noverial; Mariyati, Lely Ika (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to determine whether there is a relationship between gratitude and psychological well-being in street vendors at the Sidoarjo Sports Center. The variables contained in this study are Gratitude as the independent variable and Psychological Welfare as the dependent variable. This research was conducted at the Sidoarjo Sports Center with a total sample of 111 street vendors using the Simple Random Sampling technique. The technique in collecting data uses a modified psychological scale, namely 2 Likert scales, namely, the Gratitude scale and the Psychological Welfare Scale. The hypothesis in this study is that there is a positive relationship between gratitude and psychological well-being of street vendors at the Sidoarjo sports arena. Data analysis was performed using the Pearson correlation statistical technique with the help of SPSS 18.0 for windows. The results of data analysis in this study showed a correlation coefficient of 0.570 and a significance value of p 0.000 <0.05, so Ha was accepted. It can be concluded that there is a positive relationship between Gratitude and significant psychological well-being. It means that if Gratitude is high then Psychological Prosperity is high and vice versa if Gratitude is low then Psychological Prosperity.